2005
DOI: 10.1534/genetics.104.038232
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Disequilibrium Grouping of Single Nucleotide Polymorphisms (SNPs) Reflecting Haplotype Phylogeny for Efficient Selection of Tag SNPs

Abstract: Single nucleotide polymorphisms (SNPs) have been proposed to be grouped into haplotype blocks harboring a limited number of haplotypes. Within each block, the portion of haplotypes is expected to be tagged by a selected subset of SNPs; however, none of the proposed selection algorithms have been definitive. To address this issue, we developed a tag SNP selection algorithm based on grouping of SNPs by the linkage disequilibrium (LD) coefficient r 2 and examined five genes in three ethnic populations-the Japanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Sequences for the primer and probe sets were obtained from the JMDBase (Japan Metabolic Disease Data Base, ENPP1_6-AC, http://www.jmdbase.jp/gene_snp.asp? geneid=23101&chrnum=3), a database for metabolic disorder-related SNPs (Takeuchi et al 2005), and purchased from Applied Biosystems. All reactions were performed according to the manufacturer's protocol using TaqMan Universal PCR Master Mix, No AmpErase UNG (Applied Biosystems), with a 900 nM primer/200 nM probe final concentration and 5.0 ng genomic DNA, in a total reaction volume of 4 ll.…”
Section: Enpp1 K121q Genotypingmentioning
confidence: 99%
“…Sequences for the primer and probe sets were obtained from the JMDBase (Japan Metabolic Disease Data Base, ENPP1_6-AC, http://www.jmdbase.jp/gene_snp.asp? geneid=23101&chrnum=3), a database for metabolic disorder-related SNPs (Takeuchi et al 2005), and purchased from Applied Biosystems. All reactions were performed according to the manufacturer's protocol using TaqMan Universal PCR Master Mix, No AmpErase UNG (Applied Biosystems), with a 900 nM primer/200 nM probe final concentration and 5.0 ng genomic DNA, in a total reaction volume of 4 ll.…”
Section: Enpp1 K121q Genotypingmentioning
confidence: 99%
“…15%) SNPs. Given the low level of LD found in pine, which resulted in short LD blocks, other approaches to identify htSNPs, such as the identification of LD subgroups within LD blocks (see Takeuchi et al 2005 for details), did not perform well and are not shown.…”
Section: Methodsmentioning
confidence: 99%
“…We selected 92% of the detected SNPs as tag SNPs (n = 676) by (1) grouping SNPs with mutual r 2 C 0.6 for haplotype construction, (2) inferring haplotypes in each group, and (3) then removing redundant SNPs that are in complete LD with reference to haplotypes showing a frequency of at least 5% (Takeuchi et al 2005). Genotyping was performed either with TaqMan 1 SNP Genotyping Assays in ABI 7900HT (Applied Biosystems, Foster City, CA, USA) or with the MassARRAY 1 Compact system (Sequenom-Bruker, San Diego, CA, USA) according to the manufacturer's protocols.…”
Section: Methodsmentioning
confidence: 99%